Factors associated with knowledge and awareness on smoke-free policy at food premises: a systematic review - Dapari, Rahmat; Ahmad Kamal, Mohamad Fikri Haikal; Mariot, Monaliza; Rosle, Nor Hazimah; Muthu, Kalahvathy Tangga; Hassan, Mohd Rohaizat; Che Dom, Nazri; Syed Abdul Rahim, Syed Sharizman (Malaysian Public Health Physicians Association, 2024)
Smoke-free policy is designed to primarily protect non-smokers, as well as smokers. Food premises are considered to be hospitality areas where all segments of the population congregate, including the vulnerable groups such as children, pregnant women, and the elderly. This systematic review aims to present and systematically determine the factors associated with knowledge and awareness on smoke-free policy at food premises. We conducted an electronic search for articles related to factors associated with smoke-free policies, utilizing two databases: EBSCOhost and Scopus. Two pairs of independent reviewers screened the titles and abstracts of the collected data, stored in Microsoft Excel version 2211 against both the inclusion and exclusion criteria. Afterwards, the included articles were critically appraised to assess the quality of the studies using the Mixed Method Appraisal Tool (MMAT). Of the 332 articles identified, only four were included in the final review. Age, education level, smoking status, belief towards smoking, and location are the factors associated with knowledge and awareness of the smoke-free policy at food premises. In conclusion, smoking imposes a significant public health risk and an economic burden. Therefore, understanding the factors influencing knowledge and awareness of smoke-free policies at food premises is critical. By considering the findings from this review, policymakers can design more effective and sustainable policies that not only maximize health outcomes but also elevate the overall health status of communities.